Derived equivalences of upper-triangular ring spectra via lax limits - Jasso, Gustavo (Comptes Rendus. Mathématique)
We extend a theorem of Ladkani concerning derived equivalences between upper-triangular matrix rings to ring spectra. Our result also extends an analogous theorem of Maycock for differential graded algebras. We illustrate the main result with certain canonical equivalences determined by a smooth or proper ring spectrum.